Innovation in the Italian Counter-Reformation - McHugh, Shannon; Wainwright, Anna (Book collections on Project MUSE., 2020)
"The enduring "black legend" of the Italian Counter-Reformation, which has held sway in both scholarly and popular culture, maintains that the Council of Trent (1545-1563) ushered in a cultural dark age in Italy, snuffing out the spectacular creative production of the Renaissance. The repercussions of this cliche continue to be felt in literary studies in particular. As a result, the decades following Trent have been mostly overlooked in Italian literary studies. The thirteen essays of Innovation in the Italian Counter-Reformation present a radical reconsideration of literary production in post-Tridentine Italy. With particular attention to the much-maligned tradition of spiritual literature, the volume's contributors weave literary analysis together with religion, theater, art, music, science, and gender to demonstrate that the literature of this period not only merits study, but is positively innovative"--